Astonied: the mineral poetics of Robinson Jeffers, Hugh MacDiarmid, Francis Ponge and Muriel Rukeyser. Issue 9 (1st September 2020) - Murphet, Julian
ABSTRACT: This essay draws attention to a lyric tendency that bypassed the human subject altogether. Writing as the losses of World War Two reached unprecedented historical highs, the poet Robinson Jeffers counselled a quietist retreat into 'inhumanism', the 'philosophical shifting of emphasis of man to not-man'. Jeffers – I argue – looked back to earlier modernists to emphasise the mineral world and to celebrate its resistance to organic metaphors; its predisposition to substantive temporal endurance rather than growth and decay; its emptiness of connotation and expression; its properly fundamental properties, hidden beneath the lurid topsoil of flora and fauna; its crystalline rather than cellular structure. This essay uses work by Jeffers himself, and the poets Hugh MacDiarmid, Muriel Rukeyser, and Francis Ponge, to discuss the emergence of a new kind of poetics between 1920 and 1950; one that privileged deep over human time, was cosmic in its scope, scientific in its orientation, and suggestive of a fresh species of the sublime.